PO030 Combining informant (ad8) and patient (mace) cognitive screening. (1st December 2017) - Connon, Paul; Larner, Andrew
Abstract : Objective: To assess the combination of informant questionnaire AD8 and the Mini-Addenbrooke's Cognitive Examination (MACE) for diagnosis of dementia and cognitive impairment (MCI) in a cognitive disorders clinic. The current standard of formal cognitive assessment is unwieldy in a busy out-patient setting and thus more efficient methods of clinical evaluation with retained diagnostic accuracy are desirable. Results: Of 67 patient-informant dyads seen over 8 months (May-December 2016; F:M=33:34, 49% female; age range 26–88 years, median 64), 14 patients were diagnosed with dementia (DSM-IV-TR criteria), 32 with MCI (Petersen criteria). Using cutoffs defined in index studies (AD8 ≥2/8; MACE≤25/30), both instruments were very sensitive (>0.9) but not specific (<0.4) for diagnosis of cognitive impairment. In series ('And' rule) combination improved diagnostic specificity for little loss of sensitivity. In parallel ('Or' rule) combination maximised sensitivity but with poorer specificity. Series combination had better Youden index and correct classification accuracy than parallel combination. Predictive values were >0.7 for all combinations, with predictive summary index marginally better for parallel combination. Conclusion: The results of this pragmatic study suggest that series combination of an informant (AD8) and patient (MACE) cognitive screening instrument may improve diagnostic specificity compared to individual use of tests.